Diagnostic Accuracy of Fine Needle Aspiration Cytology as Compared to Histopathology in Parotid Gland Swelling - Tripathi, Prashant; Acharya, Kunjan; Shrivastav, Shreya; Gyawali, Bigyan Raj (Journal of Nepal Health Research Council, 2024)
Background: The diagnosis of parotid swelling is challenging and investigations like imaging and needle aspiration cytology are helpful. The objective of this study was to determine the diagnostic accuracy of fine needle aspiration cytology (FNAC) as compared to the histopathology in parotid gland swelling. Methods: It was a descriptive cross sectional study carried out in the Department of ENT-Head & Neck Surgery, Tribhuvan University Teaching Hospital, Institute of Medicine, Kathmandu by reviewing the medical record charts of the patients who had undergone surgery for parotid lesions during the study period of seven and half years. All patients whose fine needle aspiration cytology and histopathology reports were available were included in the study. The data were presented as mean, standard deviation, ratio and percentages. Microsoft excel was used for data analysis. Results: There were 75 patients included in the study. The age ranged from nine years to 78 years and the mean age being 38.3± 17.42 years. The male to female ratio was 1:1.78. The concordance rate between fine needle aspiration cytology and histopathology was 82.7%. The sensitivity and specificity of the fine needle aspiration cytology were 80% and 95% respectively. Similarly, the positive predictive and negative predictive values were 84% and 93% respectively. The diagnostic accuracy of the fine needle aspiration cytology was 91% for the parotid swelling in our study. Conclusions: The diagnostic accuracy of fine needle aspiration cytology for parotid swellings in our study was excellent. The result of fine needle aspiration cytology is helpful in deciding management plan for parotid lesions. Keywords: Benign; cytology; histopathology; malignant; parotid.